2016
DOI: 10.1103/physreva.93.031601
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of pattern-loaded fermions in bichromatic optical lattices

Abstract: Motivated by experiments in Munich (M. Schreiber et. al. Science \textbf{349}, 842), we study the dynamics of interacting fermions initially prepared in charge density wave states in one-dimensional bichromatic optical lattices. The experiment sees a marked lack of thermalization, which has been taken as evidence for an interacting generalization of Anderson localization, dubbed "many-body localization". We model the experiments using an interacting Aubry-Andre model and develop a computationally efficient low… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This increase in lifetime might be due to the reduced phase space for scattering in the hard-core limit (U J). A recent theoretical study using a cluster expansion method on a smaller system (8 × 8 sites) observed a similar trend [41].…”
mentioning
confidence: 55%
“…This increase in lifetime might be due to the reduced phase space for scattering in the hard-core limit (U J). A recent theoretical study using a cluster expansion method on a smaller system (8 × 8 sites) observed a similar trend [41].…”
mentioning
confidence: 55%
“…Half a century later, Basko et al coined the phrase 'many-body localization' showing that this insulating behavior survives weak interactions at finite temperature [26]. Further experimental and theoretical studies confirmed these results, and showed they persist under very general conditions [6][7][8][27][28][29][30][31]. One expects that generically disorder can be used to prevent entropy flow, even in the presence of interactions.…”
Section: Introductionmentioning
confidence: 98%
“…Evidence of such critical points has been reported [33][34][35][36] in experiments with ultracold atoms in disordered lattices, implementing either the fermionic or the bosonic Anderson-Hubbard model in various dimensions. From the theoretical side, numerical studies of systems with a finite density of particles have mainly focused on one-dimensional models [37][38][39][40][41][42][43][44][45], due to the high computational effort. The existence of many-body mobility edges in systems with space dimension larger than one is currently debated [46].…”
Section: Introductionmentioning
confidence: 99%